Biometrical Study Of Brine Shrimp (Artemia franciscana) With Special Emphasis On Hatching Efficiency And Hatching Percentage In Tropical Condition At Bangladesh - Nipa, Sharmin Akter; Hasan, Rajib; Naser, M Niamul; Rashid, Harun Or (European Scientific Journal, ESJ, 2016)
The present study was carried out to investigate the hatching efficiency and hatching percentage of untreated and decapsulated cysts of Artemia franciscana at three salinities; 30 ppt, 35 ppt and 40 ppt. This study revealed that the hatching efficiency and hatching percentage were higher in case of decapsulated cysts. First hatching of nauplius from cysts were observed after 14 hours and 13 hours of incubation for untreated and decapsulated cysts, respectively. The values of hatching efficiency and hatching percentage were also higher at 35 ppt in untreated and decapsulated cysts. At 35 ppt, the hatching efficiency after 48 hours of incubation was 1.42× 105 for decapsulated cysts and the value for untreated cysts was 8.96× 104 nauplii per gram cysts. After 96 hours of incubation, the hatching percentage for decapsulated cysts were 75%, 89% and 90% at 30 ppt, 35 ppt and 40 ppt, respectively; and the values were 55%, 62.5% and 60% for untreated cysts at respected salinities, 30 ppt, 35 ppt and 40 ppt. The mean diameter for untreated and chorionic cysts were 242.2±1.90 µm and 213.5±3.167 µm respectively, with a chorionic thickness of 14.35 µm. This study would help the hatchery managers to understand the efficiency of larval live feed, since adequate data are lacking on the hatching performances of Artemia cysts in Bangladesh.